2001
DOI: 10.1017/s1431927600027677
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Study of Y2O3 Nanotips Grown on LaAlO3

Abstract: Y2O3 is a super refractory oxide with high thermal stability and finds various applications in optics and microelectronic devices. Recently, Eu-activated Y2O3 films attracted much research interest due to its promising applications in flat panel field emission displays. Epitaxial Y2O3:Eu thin films have been grown on LaA1O3(LAO). in this paper we report a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Composition analysis by EDS confirmed that the tips are Y 2 O 3 and that the continuous phase between the tips is Y123. 14 The J c for this sample could not be measured, which would indicate that the Y123 film is likely to be discontinuous on a macroscopic scale because it is so thin (approximately 10 nm). Growing thicker (50 nm and greater) Y123 layers on top of Y 2 O 3 nanotip layers yields superconducting films with essentially unaffected standard Y123 properties (T c ∼ 92 K, J c ∼ 10 6 A/cm 2 at 77 K).…”
Section: B 10-nm Y123/20-nm Y 2 O 3 Bilayer Filmmentioning
confidence: 96%
“…Composition analysis by EDS confirmed that the tips are Y 2 O 3 and that the continuous phase between the tips is Y123. 14 The J c for this sample could not be measured, which would indicate that the Y123 film is likely to be discontinuous on a macroscopic scale because it is so thin (approximately 10 nm). Growing thicker (50 nm and greater) Y123 layers on top of Y 2 O 3 nanotip layers yields superconducting films with essentially unaffected standard Y123 properties (T c ∼ 92 K, J c ∼ 10 6 A/cm 2 at 77 K).…”
Section: B 10-nm Y123/20-nm Y 2 O 3 Bilayer Filmmentioning
confidence: 96%